Research on the equity of health manpower resource allocation in the Yangtze River Delta region - Li, Qinglian; Zheng, Siyuan; Jing, Zhengwei; Chen, Dingwan; Chen, Kun; Li, Yingjun (Frontiers in Public Health, 2025)
BackgroundTo analyze the equity of the current allocation of health human resources using statistical data on health resources in the Yangtze River Delta region.MethodsThe Gini coefficient quantifies the level of distributional equality, the Theil index assesses the source of inequality, and the health resource agglomeration degree (HRAD) measures the accessibility of health resources, combining the three methods to evaluate the equity of the current allocation of health human resources in the Yangtze River Delta region. Furthermore, trend analysis of fairness indicators was conducted using regression models.ResultsHuman resources for health in the Yangtze River Delta region have been increasing between 2014 and 2022. The Gini coefficient and Theil index in the Yangtze River Delta region are more equitable in terms of the distribution of healthcare resources based on population and gross domestic product (GDP) rather than geographical region. In Anhui Province, HRAD and HRAD/PAD (population agglomeration degree) were both less than 1. In Zhejiang Province, HRAD for health technicians and registered nurses was less than 1.ConclusionHuman resources for health and healthcare ratios in the Yangtze River Delta region have continued to grow. However, the equity of health resources allocated based on population and economic factors is superior to that allocated based on geographical factors, and the equity of health resource concentration remains to be improved. To address this equity issue, it is necessary to comprehensively consider various factors such as population, geography, and GDP, and formulate corresponding measures accordingly.